2013
DOI: 10.1007/s13244-013-0286-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of morphological changes in the thoracolumbar spine on whole-spine computed tomographic images

Abstract: ObjectivesThis article reviews the prevalence of lumbarisation, sacralisation and lumbar ribs, and their morphological relevance by evaluating multi-slice computed tomography (MSCT) images. These segment variations can cause miscounting of vertebrae at the lumbar spinal level.MethodsA retrospective radiographic analysis of 226 cases scanned by MSCT prior to forensic autopsy was undertaken. MSCT scans of the entire spine were obtained. Radiological data were evaluated on a three-dimensional image workstation. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Individually lumbarisation is found to be less common than sacralisation in our study which is consistent with findings of Ucer et al [25]. However, Leboeuf et al [34], Kim et al [35], Peh et al [36] and Nakajima et al [26] have reported opposite results. Individuals with lumbarisation may present clinically with pain in lower part of the back and DISCUSSION LSTV and its implications: In the present study, out of 50 dry sacra, only six (12%) showed presence of LSTV.…”
Section: Lumbarisation and Its Implicationssupporting
confidence: 91%
“…Individually lumbarisation is found to be less common than sacralisation in our study which is consistent with findings of Ucer et al [25]. However, Leboeuf et al [34], Kim et al [35], Peh et al [36] and Nakajima et al [26] have reported opposite results. Individuals with lumbarisation may present clinically with pain in lower part of the back and DISCUSSION LSTV and its implications: In the present study, out of 50 dry sacra, only six (12%) showed presence of LSTV.…”
Section: Lumbarisation and Its Implicationssupporting
confidence: 91%
“…Among nine samples of females and males combined that are reported in the literature and are not based on the Hamann‐Todd or Robert J. Terry Collections, which are the collections used in this study, the percentage of individuals with 24 PSV ranges from 75.0% to 91.2%, with a median of 85.0% (Allbrook, ; Bardeen, ; Bornstein & Peterson, ; de Beer Kaufman, ; Merbs, ; Nakajima et al, ; Stewart, ). This interpopulational variation in number of PSV is not likely an artifact of different proportions of females and males because this study and other studies show that the sexes have the same, or approximately the same, proportion of individuals with 24 PSV (Merbs, ; Nakajima et al, ; but see Stewart, ). As number of vertebrae is heritable, interpopulational variation in number of PSV could be genetically based.…”
Section: Discussionmentioning
confidence: 99%
“…Number of vertebrae, both total and within regional segments (i.e., cervical, thoracic, lumbar, sacral, and caudal) differs among primate and other mammalian species (Erikson, ; Russo & Williams, ; Sargis, ; Schultz, ; Williams, ), among populations within species (Aguirre, Walker, & Gideon, ; Shikano & Merilä, ; Slijepčević, Galis, Arntzen, & Ivanović, ; Tibblin, Berggren, Nordahl, Larsson, & Forsman, ), between sexes within species (Aguirre et al, ; Arntzen, Beukema, Galis, & Ivanović, ; Bardeen, ; Bornstein & Peterson, ; de Beer Kaufman, ; Karapetian, ; Merbs, ; Shikano & Merilä, ; Stewart, ), and among individuals within a population (Allbrook, ; Bornstein & Peterson, ; de Beer Kaufman, ; Merbs, ; Nakajima et al, ). Number of vertebrae is heritable and can evolve by natural selection (Alho, Leinonen, & Merilä, ).…”
Section: Introductionmentioning
confidence: 99%
“…The affected vertebra has combined anatomical morphology of the two adjacent vertebral regions. Thoracolumbar transitional vertebrae (TLTV) are vertebrae that result from the overlap or shift of thoracic and lumbar somites at the thoracolumbar junction (Savage, 2005;Chang et al 2007;Konin & Walz, 2010;Khairnar & Rajale, 2013;Nakajima et al 2014;Sekharappa et al 2014). This may alter the number of vertebrae present in the thoracic region (T 1 -T 11 or T 1 -T 13 ) or lumbar region (L 1 -L 4 or L 1 -L 6 ).…”
Section: Introductionmentioning
confidence: 99%